Potencial antitumoral de flavonóides isolados de plantas do nordeste brasileiro : estudos preliminares da relação estrutura-atividade citotóxica - Militão, Gardênia Carmen Gadelha (2005)
In searching for anticancer compounds derived from plant sources, 18 flavonoids were assayed for their cytotoxic potentials and the results were compared for structure-activity relationship purposes. The flavonoid group was subdivided in flavones and pterocarpans. The cytotoxic activity was initially evaluated on tumor cell lines, through the MTT assay, and on sea urchin eggs development. The pterocarpans showed a consistently higher activity on both assays. For the flavones, some structure-activity observations can be highlighted: a) a hydroxyl instead of a methoxyl group on C4 and C5 positions increases activity; b) a hydroxyl and a sugar on C3 position decreases activity and, by the data acquired, it can be emphasized that the methoxyl on C3 increases activity and c) the methoxyl on C7 position increases activity. The pterocarpans, a methoxyl group on C2 position increases the cytotoxic activity. Since the 2,3,9- trimethoxypterocarpan showed the best results in both assays, mode of action studies were conducted for the non-prenylated pterocarpans as an attempt to understand the influence of these groups over their bioactivity. All pterocarpans tested reduced cell viability, as indicated by the trypan blue assay, except for the 3,10-dihydroxy-9-methoxypterocarpan at 12,5 micrograma/mL. They also inhibited DNA synthesis and 2,3,9-trimethoxypterocarpan induced morphological cell alterations, which could be suggestive of apoptosis. On the assays for induction of cellular apoptosis this same compound caused DNA fragmentation and mitochondria depolarization, therefore maintaining membrane integrity, typical apoptotic signs. The other compounds, besides DNA fragmentation, there was noticeable loss of membrane integrity on higher concentrations, an indicative cell death by necrosis. Based on these observations, it is conclusive that the methoxyl group on C2 position is an important pharmacophoric unit for pterocarpans, which emerge as a potential class of anticancer chemicals.